Kinship in ancient Athens an anthropological analysis - Humphreys, Sarah C. 1934- (Oxford scholarship online, 2019)
The concept of kinship is at the heart of understanding the structure of ancient Athenian society and the lives of its citizens. Drawing on epigraphic, literary, and archaeological sources, 'Kinship in Ancient Athens' explores interactions between kin across a range of social contexts, from family life to legal matters, politics, and more